ALK gene translocations and amplifications in brain metastases of non-small cell lung cancer - Preusser, Matthias; Berghoff, Anna S.; Ilhan-Mutlu, Ayseguel; Magerle, Manuel; Dinhof, Carina; Widhalm, Georg; Dieckmann, Karin; Marosi, Christine; Wöhrer, Adelheid; Hackl, Monika; Zöchbauer-Müller, Sabine; Deimling, Andreas von; et al. (Lung cancer, 2013)
Background - Increased incidence of brain metastases (BM) in non-small cell lung cancer (NSCLC) with ALK translocations was postulated, however, ALK gene aberrations in NSCLC-BM have not been investigated so far. - Methods - We investigated ALK and EML4 gene aberrations (amplifications, translocations, inversions) by fluorescent in situ hybridization (FISH) (n=175) and ALK and EML4 protein expression by immunohistochemistry (n=221) in NSCLC BM and corresponding primary tumors. - Results - ALK translocations were found in 4/151 (2.6%; 3 of them involving EML4) of BM of adenocarcinomas (AC), 1/9 (11.1%) of adenosquamous carcinomas (ASC), 0/5 of squamous cell carcinomas (SCC) and 0/10 of large cell carcinomas (LCC). Rearrangement of ALK without involvement of EML4 was seen in 1 AC-BM and rearrangement of EML4 without involvement of ALK in 3 AC-BM, 1 ASC-BM and 1 LCC. ALK amplifications without gene rearrangements were found in BM of 16/151 (10.6%) AC, 2/5 (40%) SCC, 0/9 ASC and one LCC. ALK translocation status was constant between BM and primary tumors in 16 evaluable cases including two cases with ALK-EML4 translocations Among these 16 cases ALK amplification was seen in two BM and none of the primary tumors. All cases with translocations but not with amplifications of ALK showed protein expression. We found no association of ALK gene status with patient age, gender or overall survival time. - Conclusions - ALK translocations and amplifications are found in approximately 3% and 11% of NSCLC-BM, respectively. While ALK translocations appear to be constant between primary tumors and BM, amplifications seem to be more prevalent in BM. ALK translocation, but not ALK amplification is associated with ALK protein overexpression. Further studies are needed to determine whether NSCLC-BM patients with ALK gene aberrations may benefit from specific inhibitor therapy.